Human Resource Orientation in Improving Work Performance in Schools - Ruba'i, Muhammad -; Al Idrus, S Ali Jadid; Thohri, Muhammad (JUPE : Jurnal Pendidikan Mandala, 2023)
Work performance is the behavior and work outcomes that principals, teachers, and students engage in or bring to the table in relation to contributing to organizational goals. Students who are satisfied with their learning will bring good performance. Likewise, teachers who have principals with good human resources will improve work performance for the better. The purpose of the research is to find out the orientation of human resources in improving work performance in schools. This research method is descriptive qualitative with data sources from literature (library research) through content analysis on various books, journals, and theses both research and conceptual results. The results of this paper conclude that human resource orientation in improving work performance in schools needs to be done by principals because principals are educational leaders who play an important role in improving teacher work performance. In order for educational goals to be achieved, educational institutions should be managed professionally with good human resources so that they can improve better work performance.